2015
DOI: 10.5812/ijpbs.2074v3
|View full text |Cite
|
Sign up to set email alerts
|

Iranian Common Attitude toward Opium Consumption

Abstract: Iran is suffering from the 2 nd most severe addiction to opioids in the world. While the explanation of this enormous drug problem is refutably related to drug trafficking, the drug dilemma also illustrates the chain reaction of the imposed war with Iraq in 1980 -88; the problems of poverty, unemployment, urbanization, homelessness, adultery, family crises, divorce, domestic violence, and runaway children. Although opium addiction often linked to these factors, drug use is common among all social classes. It s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Although, because of all the restrictions, alcohol usage in Iran is significantly lower than in many other countries (World Health Organization 2014), the use of opium and opium residue is much higher in Iran. In fact, Iran is currently ranked second in the world for severe addiction to opioids (Zarghami 2015). The Iranian Drug Control Headquarters estimated that, in 2015, as many as 2.8 million Iranians aged 15-64 years old were addicted to illicit drugs.…”
Section: Participantmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, because of all the restrictions, alcohol usage in Iran is significantly lower than in many other countries (World Health Organization 2014), the use of opium and opium residue is much higher in Iran. In fact, Iran is currently ranked second in the world for severe addiction to opioids (Zarghami 2015). The Iranian Drug Control Headquarters estimated that, in 2015, as many as 2.8 million Iranians aged 15-64 years old were addicted to illicit drugs.…”
Section: Participantmentioning
confidence: 99%
“…Even though addiction to opioids is often associated with biopsychosocial factors, it was also found that drug use is common among all social classes in Iran. One reason for this appears to be the positive traditional attitude towards raw opium use (Zarghami 2015). Nevertheless, there is no known study of substance misuse among gay men living in Iran.…”
Section: Participantmentioning
confidence: 99%
“…Afghanistan and Iran also have the highest rate of opium seizure in the world . The third reason is the cultural acceptability and fewer stigmas towards opium in these regions due to long‐standing use of the substance in the region, in many cases as a medicine , which can eventually increase the compliance of patients with the treatment. In a qualitative study among 52 patients receiving OT, reported reasons for switching to OT were dependence on methadone, the chemical nature of methadone and long duration of methadone treatment, as opposed to the herbal nature of OT, its ability to improve general health as well as treatment of craving and withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…The most common type of substance addiction among Iranian women is opium (Ghazavi, Mosayebi, Solhi, Rafiei, & Moazzeni, 2013; Maghsoudlou et al, 2018; Saleh Gargari et al, 2011; Sharifian et al, 2011; Soltaninejad & Shadnia, 2018; Zarghami, 2015). Opium contains more than 40 types of alkaloids, including morphine, codeine, and thebaine as well as 70 other components, such as sugars and organic acids (Ghazavi, Mosayebi, et al, 2013; Yarahmadzehi, Fanaei, Mirshekar, & Atashpanjeh, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Opium contains more than 40 types of alkaloids, including morphine, codeine, and thebaine as well as 70 other components, such as sugars and organic acids (Ghazavi, Mosayebi, et al, 2013; Yarahmadzehi, Fanaei, Mirshekar, & Atashpanjeh, 2020). Opium is traditionally used in Iran for pleasure or treatment, such as the treatment of diarrhea, insomnia, and pain relief (Ghazavi, Mosayebi, et al, 2013; Zarghami, 2015).…”
Section: Introductionmentioning
confidence: 99%